2014
DOI: 10.1063/1.4867343
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of the magnetostrictive properties of cobalt ferrite on the initial powder particle size distribution

Abstract: The dependence of the magnetostrictive properties of cobalt ferrite on the size distribution of thepowder used in deriving the samples from traditional ceramic approach is presented. Sample obtained by combining the smallest and largest particle size distributions gave the highestmagnetostriction and strain sensitivity (216 ppm and 1.34 nm/A, respectively), for measurementin parallel direction but the least (66 ppm and 0.38 nm/ A respectively) in perpendicular direction. Sample derived from largest particle si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 6 publications
3
10
0
Order By: Relevance
“…The latter can be defined as q l = dk/dH, where k is the magnetostriction. 23 For polycrystalline CoFe 2 O 4 the magnitude of the longitudinal magnetostriction exhibits a nonmonotonic field dependence, reaching a maximal value approximately at 0.15-0.20 T for bulk, 24 which is comparable to the peaks we observed between 0.13 and 0.18 T for the longitudinal ME effect in Fig. 7.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…The latter can be defined as q l = dk/dH, where k is the magnetostriction. 23 For polycrystalline CoFe 2 O 4 the magnitude of the longitudinal magnetostriction exhibits a nonmonotonic field dependence, reaching a maximal value approximately at 0.15-0.20 T for bulk, 24 which is comparable to the peaks we observed between 0.13 and 0.18 T for the longitudinal ME effect in Fig. 7.…”
Section: Resultssupporting
confidence: 83%
“…Figure 6 illustrates the effect of poling on the magnetoelectric effect. 23 For polycrystalline CoFe 2 O 4 the magnitude of the longitudinal magnetostriction exhibits a nonmonotonic field dependence, reaching a maximal value approximately at 0.15-0.20 T for bulk, 24 which is comparable to the peaks we observed between 0.13 and 0.18 T for the longitudinal ME effect in Fig. The depoled sample shows a random and noisy ME response with very small values of electrically induced magnetization, M ME < 0.4 A/m.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these, grain/particle size and their distributions are most of the important factors governing the magnetic properties in the nanomaterials. Nlebedim et al [17] observed that the particle size distribution of CoFe 2 O 4 (Co-ferrite) is an important factor in controlling the magnetostictive properties. Malik et al [18] observed double peaks in the zero field cooled and field cooled magnetic measurements performed at low field due to bimodal particle size distribution in Ni-ferrite nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…The physical properties of these nanoparticles can also be easily tailored by controlling its microstructure and enabling them for many applications [13][14][15]. The sizes of the nanoparticles [14,16], morphology [7,13], size distribution [17][18][19], packing density [20], intergranular exchange interaction [21][22][23], and cation distribution [24,25] are some of the factors which are responsible for the modified magnetic properties in the nanomaterials. Among these, grain/particle size and their distributions are most of the important factors governing the magnetic properties in the nanomaterials.…”
Section: Introductionmentioning
confidence: 99%